KINERJA PEMBELAJARAN GURU PADA SD NEGERI BARAYA I KEC. BONTOALA KOTA MAKASSAR - Erniyanti, Erniyanti (Pascasarjana Universitas Negeri Makassar, 2016)
Supervision Functions of the principals in improving elementary school teachers’ performance in bontoala subdistrict of Makassar. The study aimed at describing the steps on the implementation of supervision in terms of supervision plan, supervision implementation, and follow-up supervision as well as the principal in improving teachers` performance. The study employed qualitative research method. The study was conducted at SDN Baraya 2 Makassar and SDN laying 1 Makassar in Bontoala subdistrict in Makassar. Data were collected through interview, observation, and documentation. Data were analyzed by conducting data collection, data reduction, data display, and data verification by conclusion drawing. The result of the study revealed that the supervision functions of the principals at SDN Baraya 2 Makassar and SDN Layang 1 Makassar which consisted of supervision plan, supervision implementatation, and follow-up supervision as well as the efforts conducted in improving teachers’ performanc had not been implemented maximally based on supervision competence dimension of the principals.